Towards ‘An Intellectual Capital-Based View of the Firm’: Origins and Nature - Martín de Castro, Gregorio (Journal of business ethics, 2011)
Economic and social activities are undergoing radical changes, which can be labelled as ‘knowledge economy and/or society’. In this sense, intellectual capital (IC), or knowledge assets, as the fourth factor of production, is replacing the other ones – job, land and capital. This article tries to offer the origins and nature of the firm’s IC that can be labelled as ‘An Intellectual Capital-Based View of the Firm Competition’. This framework tries to highlight the strategic role of different intangible assets like talented and committed workers, cultural values, or long-term relationships among the firm and its stakeholders – customers, allies, suppliers and society in general – in gaining and sustaining competitive advantages, being the management of IC a key issue in the management agenda.